Preparation of Performance Audit Guidelines to Improve the Capabilities of Government Internal Supervision Apparatus (Case Study on the Inspectorate of the Indonesian Maritime Security Agency) - Toba Antanov Simangunsong; Adam Zakaria; Unggul Purwohedi (PT. Publikasiku Academic Solution, 2025)
The results of the evaluation by BPKP on the capabilities of APIP Bakamla for the last three years until now show that APIP's capabilities for the Role and Service elements are still at level 2 (two) where the parameters of the implementation of the performance audit have not been met. This problem arises because the Bakamla Inspectorate does not have technical guidelines on procedures for carrying out good performance audits. Therefore, the researcher helps to develop technical guidelines for performance audits that assess the economic, efficiency, and effectiveness aspects (3E) aspects of the implementation of the main tasks and functions of work units within the Maritime Security Agency. The goal to be achieved is the drafting of performance audit guidelines at the Bakamla Inspectorate so that the Bakamla Inspectorate can conduct performance audits in accordance with applicable regulations. This performance audit guideline includes starting from the stages of Performance Audit Planning, Performance Audit Implementation, and Preparation of Performance Audit Results Report. This research is an applied research that aims to address real problems faced in the world of practice, both individuals, communities, and organizations. This research uses a project-based scheme, namely carrying out activities in the form of projects that aim to provide solutions to problems faced by the Bakamla Inspectorate. The scope of the research is the application of performance audits at the Bakamla Inspectorate. The result of this research is the issuance of the Decree of the Head of the Maritime Security Agency of the Republic of Indonesia Number 174 of 2025 dated May 27, 2025 concerning Technical Guidelines for Performance Audit of the Maritime Security Agency of the Republic of Indonesia and has been implemented through the Decree of the Head of the Maritime Security Agency Number: PW.03/530/2025 dated June 10, 2025 concerning the implementation of performance audit activities at the Directorate of Research and Development of Bakamla RI in 2025. The implementation of this performance audit will certainly have an impact on increasing APIP's capabilities on the Role and Service elements to level 3 (three).